Aromatase Expression Increases the Survival and Malignancy of Estrogen Receptor Positive Breast Cancer Cells - Mukhopadhyay, Keya De (PLoS One, 2015)
In postmenopausal women, local estrogen produced by adipose stromal cells in the breast is believed to support estrogen receptor alpha (ERα) positive breast cancer cell survival and growth. This raises the question of how the ERα positive metastatic breast cancer cells survive after they enter blood and lymph circulation, where estrogen level is very low in postmenopausal women. In this study, we show that the aromatase expression increased when ERα positive breast cancer cells were cultured in suspension. Furthermore, treatment with the aromatase substrate, testosterone, inhibited suspension culture-induced apoptosis whereas an aromatase inhibitor attenuated the effect of testosterone suggesting that suspended circulating ERα positive breast cancer cells may up-regulate intracrine estrogen activity for survival. Consistent with this notion, a moderate level of ectopic aromatase expression rendered a non-tumorigenic ERα positive breast cancer cell line not only tumorigenic but also metastatic in female nude mice without exogenous estrogen supplementation. The increased malignant phenotype was confirmed to be due to aromatase expression as the growth of orthotopic tumors regressed with systemic administration of an aromatase inhibitor. Thus, our study provides experimental evidence that aromatase plays an important role in the survival of metastatic ERα breast cancer cells by suppressing anoikis.